Orientasi Pendidikan Pesantren Kepada Masyarakat Buruh Desa Berbek Kecamatan Waru Kabupaten Sidoarjo - Kholid, Ihyaul (Jurnal Keislaman, 2021)
This journal is the result of Ihyaul Kholid's research entitled "Orientation of Islamic Boarding School Education to the Labor Community of Berbek Village, Waru District, Sidoarjo Regency". In this study, the authors tried to enter the Kaafiz Zamaan Islamic boarding school to collect accurate data from the pesantren, both in the form of primary data and secondary data. Through a phenomenological approach, the author can find two phenomena that are fully optimal. From observations made by researchers, it can be concluded that the orientation of pesantren education in the Berbek Waru Sidoarjo labor community will produce several changes including: Controlling the administration of the Kaafiz Zamaan Islamic Boarding School both AD/ART, structural management, data for teachers and students. Making the Kaafiz Zamaan Islamic Boarding School a center for religious and scientific activities, such as PHBI 1 Muharram, Megengan commemoration, National Santri Day commemoration, Prophet Muhammad's Birthday commemoration, Nishfu Sa'ban commemoration, Isra 'Mi'raj commemoration and Nuzulul Qur'an commemoration. Growing the younger generation, especially children of the working community, to learn the Koran at TPQ Pondok Pesantren Kaafiz Zamaan through extra al-banjari training. Recruiting the adult generation, especially the ladies and gentlemen, to love learning about Islam through the socialization of the yasin-tahlil congregation and PHBI moments.